The Effect of Good Corporate Governance and Free Cash Flow on Company Performance - Ilham Nugrahanto Raharjo; Rina Trisnawati (Pusat Riset dan Inovasi Nasional, 2023)
Manufacturing companies should have free cash flow (FCF) available where the remaining cash owned by the Company as a reserve fund when the Company is in an urgent situation can be used. With the FCF, the Company does not need to worry about dividend distribution to investors. The smooth distribution of the Company is a sign that the Company's performance is in good condition. This study aims to analyze the effect of good corporate governance and free cash flow on company performance. This research uses quantitative methods. This study uses the object of basic material companies listed on the IDX in 2018-2021. The source of the financial statement data used comes from the website of each company or idx.co.id. The population is essential material companies listed on the Indonesia Stock Exchange (IDX). Sampling technique with purposive sampling. The number of samples is 43 companies. This research analysis method uses computer assistance through the SPSS program. The results of this study show that the Board of Directors has a positive and insignificant effect on Company Performance. The Board of Commissioners has a positive and little impact on Company Performance. The Audit Committee does not affect Company Performance. Free Cash Flow has a positive and insignificant effect on Company Performance. The Board of Directors, Board of Commissioners, and Audit Committee variables have a positive and little effect on Company performance, while the Audit Committee has no effect on performance.